APPLICATION FRAUD PENTAGON FOR DETECTING SYMPTOMS OF SHORTFUL FINANCIAL STATEMENTS - Driya Sudaryono (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The purpose of this study is to determine the effect of fraud pentagon toward fraudulent financial reporting sympton using modified Jones model to the mining companies. The method of sampling used purposive sampling method. The sample consists of 30 companies was listed on the Indonesia Stock Exchange in 2013-2016. The result of this research concluded that pressure which proxied by financial target and financial stability has a positive and significant effect on fraudulent financial reporting. Opportunity has a negative and significant effect on fraudulent financial reporting. Rationalization, capability, and arrogance has not significant effect on fraudulent financial reporting.